INCLUSIVE CARE MODELS ELDERLY HEALTHCARE: A SYSTEMATIC LITERATURE REVIEW - Yulia; Gusni Rahma (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
This study applied a Systematic Literature Review (SLR) to identify, appraise, and synthesize open-access empirical evidence on inclusive care models in elderly healthcare. The review followed PRISMA 2020 and searched PubMed, Scopus, Web of Science, DOAJ, and Google Scholar for studies published between 2015 and 2025. Eligible articles were original research (quantitative, qualitative, or mixed methods) focusing on service delivery or care models for older adults and explicitly addressing inclusivity, integration, person-centeredness, or collaborative care, with full-text availability in English or Indonesian. From 1,280 records, 1,010 unique articles were screened, 80 full texts were assessed, and 10 studies were included in the final synthesis. Across studies, inclusive elderly care was most consistently implemented through integrated, person-centred, team-based delivery combining comprehensive assessment, individualized care planning, coordinated follow-up, and cross-sector collaboration. Stronger benefits were typically observed among frail older adults when care intensity was aligned with comlplex needs by risk stratification and case management. Mental health integration emerged as a critical component for community-dwelling older adults, supporting the integration of psychological care into routine elderly healthcare pathways rather than parallel programs. Evidence from institutional settings indicated that partnership-based models involving nurses, caregivers, and older adults can improve functional outcomes. Overall, the findings support scaling integrated community and institutional partnership approaches, while future research should strengthen reporting on implementation fidelity, equity impacts, and cost-effectiveness to guide sustainable adoption of inclusive, gerontic-friendly care models.